2019
DOI: 10.1073/pnas.1821455116
|View full text |Cite
|
Sign up to set email alerts
|

Motor primitives are determined in early development and are then robustly conserved into adulthood

Abstract: Motor patterns in legged vertebrates show modularity in both young and adult animals, comprising motor synergies or primitives. Are such spinal modules observed in young mammals conserved into adulthood or altered? Conceivably, early circuit modules alter radically through experience and descending pathways' activity. We analyze lumbar motor patterns of intact adult rats and the same rats after spinal transection and compare these with adult rats spinal transected 5 days postnatally, before most motor experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 60 publications
(130 reference statements)
5
60
1
Order By: Relevance
“…7c). Recent data from multiple model vertebrates have shown convincingly that locomotor W's and C(t)'s are encoded by spinal interneuronal networks 8,19,44,45 . Results from human survivors of stroke 46,47 and spinal cord injury 48 also partially support the subcortical origin of the locomotor synergies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7c). Recent data from multiple model vertebrates have shown convincingly that locomotor W's and C(t)'s are encoded by spinal interneuronal networks 8,19,44,45 . Results from human survivors of stroke 46,47 and spinal cord injury 48 also partially support the subcortical origin of the locomotor synergies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that these constraints assume a modular architecture that facilitates the coordination and execution of diverse motor behaviors 6 . Recent studies have shown that for at least some of these modular constraints, called motor primitives or motor modules, their structures appear to be either inborn 7 or determined very early in life 8 . Indeed, many of them remain rather invariant over most of the life span 5,8 or even across species 7 .…”
mentioning
confidence: 99%
“…Neurophysiological studies in frogs (2,13,14), mice (15), rats (16,17), cats (18), and monkeys (8) support the idea that the temporal activation patterns and the muscle synergies derived from EMG recordings reflect the output of spinal networks of premotor interneurons. Indeed, the modular EMG organization is preserved after complete spinal cord lesions in animals (19)(20)(21) and humans (22,23).…”
mentioning
confidence: 99%
“…They include four main sequential activations of muscle synergies timed at a specific phase of the step cycle, corresponding to limb touch-down, propulsion, lift-off, and swing (7,11,15,17,22,27). While the neuromuscular modules of adult locomotion have been thoroughly investigated (9,17,20,22,28,29), there is still limited knowledge about their development since birth (11,21,30,31). Here we consider the development of human locomotion.…”
mentioning
confidence: 99%
“…Hierarchical temporal structures might arise during development in a variety of ways (Dominici et al 2011;Yang et al 2019). One way is that a single protosequence is learnt first.…”
Section: From Serial To Hierarchical Modellingmentioning
confidence: 99%